2017
DOI: 10.1111/jsr.12585
|View full text |Cite
|
Sign up to set email alerts
|

Association between left atrial enlargement and obstructive sleep apnea in a general population of 71‐year‐old men

Abstract: Left atrial enlargement has been shown to be associated with obstructive sleep apnea in patients with coronary artery disease and in sleep clinic cohorts. However, data from the general population are limited. The aim of this study was to investigate whether there is an association between obstructive sleep apnea and left atrial enlargement in a random sample from a general population of 71-year-old men. As part of the longitudinal population study The Study of Men Born in 1943, we analysed cross-sectional dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Often, patients with HFpEF present only increased wall thickness of the LV or the size of LA, which makes it even more difficult to diagnose. In our study, LA diameter was higher in patients with HFmrEF ( p = 0.0002), similar to other publications [40]. Moreover, the role of the left atrium in modulating LV function is well-known [41], and there are considerable amounts of data demonstrating that the size of the LA is directly proportional to the increased risk of cardiovascular events; this parameter is not used enough in clinical practice to determine the HF progression [42].…”
Section: Discussionsupporting
confidence: 92%
“…Often, patients with HFpEF present only increased wall thickness of the LV or the size of LA, which makes it even more difficult to diagnose. In our study, LA diameter was higher in patients with HFmrEF ( p = 0.0002), similar to other publications [40]. Moreover, the role of the left atrium in modulating LV function is well-known [41], and there are considerable amounts of data demonstrating that the size of the LA is directly proportional to the increased risk of cardiovascular events; this parameter is not used enough in clinical practice to determine the HF progression [42].…”
Section: Discussionsupporting
confidence: 92%
“…Left atrial enlargement is reported in 18% of newly diagnosed OSA patients [7], being more common among subjects with moderate-to-severe OSA (52.1%) than in patients with the apnea-hypopnea index (AHI) <15 (31%; p < 0.001) [8]. The left atrial diameter is higher in patients with severe OSA than in subjects with mild sleep apnea (36.1 ± 5.7 mm versus 32.8 ± 2.3 mm; p < 0.01) [9].…”
Section: Introductionmentioning
confidence: 99%
“…The left atrial diameter is higher in patients with severe OSA than in subjects with mild sleep apnea (36.1 ± 5.7 mm versus 32.8 ± 2.3 mm; p < 0.01) [9]. Several studies showed that both indexed left atrial volume (LAVI) [1014] and left atrial area (LAA) [8] increase with OSA severity (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations